Strengthening leadership for the improvement of personal and professional performance in parataxonomists of an environmental NGO - Marín-Romero, Alejandro; Ruiz-Chaves, Warner (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To recognize the importance of leadership to optimize the performance of parataxonomists and identify the leadership skills existing in this population.MATERIAL AND METHOD: A qualitative approach was used with action-research (AR) as the main method. Semi-structured interviews and a questionnaire were applied to understand the leadership skills of the parataxonomist staff as part of a felt need to improve the performance of these people so that the results of one of the AR phases are reported.RESULTS: They show motivation and proactivity in the staff, but also situations to improve in commitment and respect for limits. Communication and collaboration need improvement, as well as digital literacy is adequate on mobile devices, but presents difficulties with the software and hardware of stationary devices.CONCLUSIONS: Leadership is crucial at all levels of the NGO, especially for parataxonomists. Sustainable leadership needs to be strengthened, and a positive attitude and outlook need to be improved.
Keywords: leadership; organizational sustainability; parataxonomist; skills; NGO.